Wavelet methods for a weighted sparsity penalty for region of interest tomography. (21st January 2015) - Klann, Esther; Quinto, Eric Todd; Ramlau, Ronny
Abstract: We consider region of interest (ROI) tomography of piecewise constant functions. Additionally, an algorithm is developed for ROI tomography of piecewise constant functions using a Haar wavelet basis. A weighted ℓ p –penalty is used with weights that depend on the relative location of wavelets to the region of interest. We prove that the proposed method is a regularization method, i.e., that the regularized solutions converge to the exact piecewise constant solution if the noise tends to zero. Tests on phantoms demonstrate the effectiveness of the method.